Pengaruh Kesesuaian Kompensasi, Asimetri Informasi, dan Komitmen Organisasi Terhadap Kecenderungan Kecurangan (Fraud) Akuntansi Pada Lembaga Perkreditan Desa (LPD) Kecamatan Tampaksiring - Ariati, Ni Wayan; Dharmayasa, I Putu Arya (Jurnal Pendidikan Ekonomi Undiksha, 2023)
This study aims to determine the effect of suitability of compensation, information asymmetry, and organizational commitment on the tendency of accounting fraud at the Village Credit Institution (LPD) in Tampaksiring District. This research is a causal quantitative research using purposive sampling technique. The number of samples used in this study were 102 respondents from a total population of 181 respondents. The data collection instrument used was a questionnaire with data analysis techniques using multiple linear regression analysis. The results of this study are: (1) Appropriate Compensation, Information Asymmetry, and Organizational Commitment have a positive and significant effect on the Tendency of Fraud Accounting (2) Compensation Appropriate has a positive and significant effect on the Tendency of Fraud Accounting (3) Information Asymmetry has an effect positive and significant towards the Tendency of Fraud Accounting (4) Organizational Commitment has a positive and significant effect on the Tendency of Fraud Accounting.